2005
DOI: 10.1016/j.mseb.2005.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Heterovalent cation-substituted Aurivillius phases, Bi2SrNaNb2TaO12 and Bi2Sr2Nb3−xMxO12 (M=Zr, Hf, Fe, Zn)

Abstract: We describe the synthesis and structural characterization of new aliovalent cation-substituted n = 3 Aurivillius phases of the formulas, Bi 2 SrNaNb 2 TaO 12 (I), Bi 2 Sr 2 Nb 2 ZrO 12 (II), Bi 2 Sr 2 Nb 2.5 Fe 0.5 O 12 (III) and Bi 2 Sr 2 Nb 2.67 Zn 0.33 O 12 (IV). Energy dispersive X-ray (EDX) investigation of the chemical compositions showed that while cation-stoichiometric materials are formed for I and II, single-phase materials are obtained only for the compositions given for III and IV suggesting that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Recently, Sivakumar and Gopalakrishnan [9] have shown it is possible to form Aurivillius-type oxides from layered Ruddlesden-Popper or Dion-Jacobson type oxides by metathesis reactions with PbBiO 2 Cl. The same group also recently reported that reaction of n ¼ 2 Aurivillius oxide SrBi 2 Nb 2 O 9 with the perovskite NaTaO 3 yielded the n ¼ 3 oxide SrNaBi 2 Nb 2 TaO 12 under mild conditions [10]. These studies demonstrate that it is possible to build-up complex inorganic structures from simpler building blocks, in a manner analogous to that routinely used in molecular systems.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Recently, Sivakumar and Gopalakrishnan [9] have shown it is possible to form Aurivillius-type oxides from layered Ruddlesden-Popper or Dion-Jacobson type oxides by metathesis reactions with PbBiO 2 Cl. The same group also recently reported that reaction of n ¼ 2 Aurivillius oxide SrBi 2 Nb 2 O 9 with the perovskite NaTaO 3 yielded the n ¼ 3 oxide SrNaBi 2 Nb 2 TaO 12 under mild conditions [10]. These studies demonstrate that it is possible to build-up complex inorganic structures from simpler building blocks, in a manner analogous to that routinely used in molecular systems.…”
Section: Introductionmentioning
confidence: 61%
“…Mandal et al [10] recently postulated that the incorporation of cations, such as Sr, that lack a s 2 lone pair electron into the perovskite slabs may force the structure to remain centrosymmetric. The demonstration here that the oxides ASrBi 2 Nb 2 TiO 12 where the perovskite-type A site contains appreciable amounts of alkaline earth cations and have structures that can be refined in the non-centrosymmetric space group B2cb demonstrates this postulate to be incorrect.…”
Section: Article In Pressmentioning
confidence: 99%
“…The B(2) sites (terminal octahedra) are preferentially occupied by Nb (Nb/Ta: 74/26) and the B(1) sites (central octahedra) by Ta (Nb/Ta: 52/48). According to[14], a reference to which is made in[13], a similar distribution of Nb and Ti cations over the sites is observed for the three-layer Aurivillius phases of the formula Bi 2 Sr 2 Nb 2 TiO 12 . The neutron Rietveld refinement for the threelayer Aurivillius phases Bi1.8 Sr 2.2 Nb 2.2 Ti 0.8 O 12 , has determined a slight preference of Nb for the B(2) sites (Nb/Ti: 78/22) in comparison with the inner B(1) site (Nb/Ti: 64/36)…”
mentioning
confidence: 59%
“…The distribution of octahedral cations over the nonequivalent sites in the perovskite-like block for the three-layer Aurivillius phases Bi 2 SrNaNb 2 TaO 12 and Bi 2 Sr 2 Nb 2.5 Fe 0.5 O 12 is investigated in [13]. The occupation of sites was determined by the Rietveld refinement of the powder X-ray diffraction data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation